2020
DOI: 10.1029/2019gl085408
|View full text |Cite
|
Sign up to set email alerts
|

The 2019 MW 5.7 Changning Earthquake, Sichuan Basin, China: A Shallow Doublet With Different Faulting Styles

Abstract: The increased seismic activity of the last ~10 years in Changning county of Sichuan Province comprised just small (mostly ML < 5.0) injection‐induced earthquakes. The MW 5.7 earthquake on June 17, 2019, is the largest event ever reported there. Moment tensor of the mainshock was remarkably dominated by a compensated linear vector dipole. We resolve its fine structure showing it was a doublet, allowing approximation by a thrust‐ and strike‐slip subevent. The mainshock nucleated as thrust faulting, which (togeth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…The epicenter of the M6 Changning earthquake was located within the well salt mine area, had a focal depth of 4-5 km (CMT depth of 3.3 km), and is thus a potential case of injection-induced earthquake (Lei et al, 2019b). A later study suggested that the earthquake was initiated at~4 km along a thrust fault, then jumped to a near-vertical strike-slip fault (Liu and Zahradník, 2020). Ten reliable focal mechanism solutions for earthquakes of M W >4 were used to estimate the directions of three principal stress axes, stress shape ratio (ϕ=(σ 2 −σ 3 )/(σ 1 −σ 3 )), and pore pressure required to reactivate the source faults.…”
Section: Seismicity In Shuanghe Salt Mine Areamentioning
confidence: 99%
“…The epicenter of the M6 Changning earthquake was located within the well salt mine area, had a focal depth of 4-5 km (CMT depth of 3.3 km), and is thus a potential case of injection-induced earthquake (Lei et al, 2019b). A later study suggested that the earthquake was initiated at~4 km along a thrust fault, then jumped to a near-vertical strike-slip fault (Liu and Zahradník, 2020). Ten reliable focal mechanism solutions for earthquakes of M W >4 were used to estimate the directions of three principal stress axes, stress shape ratio (ϕ=(σ 2 −σ 3 )/(σ 1 −σ 3 )), and pore pressure required to reactivate the source faults.…”
Section: Seismicity In Shuanghe Salt Mine Areamentioning
confidence: 99%
“…Within this context, the Changning earthquake sequence struck the southwest of the Sichuan basin for more than 2 weeks ( Figure 1b). The sequence began with a Ms 6.0 earthquake on 17 June 2019 and comprised five M5 + events and~600 minor earthquakes (Lei et al, 2019b;Liu & Zahradník, 2020;Yi et al, 2019), which has caused 13 deaths and injured more than 200 people. The spatial proximity of the sequence to HF operations in the Changning shale gas play (<10 km) raised an extensive controversy over a potential relationship with shale gas exploration.…”
Section: Introductionmentioning
confidence: 99%
“…Similar scenario could be associated with nuclear explosions, where a volumetric explosion may trigger slip on nearby faults (e.g., Mustać et al, 2020). Although the estimation of CLVD and its interpretation are quite challenging, it has been associated with interesting phenomena, such as volcanic activities, fluid motions, tensile cracks, and fault complexity (see recent examples in Fontaine et al, 2019;Liu & Zahradník, 2020;White et al, 2019). The challenge is related to both low resolution of the kernel-which is discussed in this study-and the incompleteness of Earth structure, noise in the data, poor station coverage, and misalignment of real and synthetic data, which could result in spurious high values for CLVD (Dahm et al, 1999;Frohlich, 1994Frohlich, , 1995Hejrani et al, 2017;Jechumtálová & Šílený, 2001;Roessler et al, 2007;Vavrycuk, 2007;Weber, 2006).…”
Section: A Caldera Collapsementioning
confidence: 90%
“…Our synthetic test represents a case where a strike-slip earthquake triggers a thrust fault at depth 1 km. This test is inspired by realistic occurrences of earthquakes with complex ruptures (see examples from recent studies, Liu & Zahradník, 2020;Sokos et al, 2020). To simulate a "complex" rupture, two subevents separated by 20 km horizontally and 12 s in time are simulated and their waveforms are added together (Figure 10a).…”
Section: Complex Shallow Earthquakesmentioning
confidence: 99%
See 1 more Smart Citation